Antecedents and Consequences of Project Team Cross-Functional Cooperation - Pinto, Mary Beth; Pinto, Jeffrey K.; Prescott, John E. (Management Science, 1993)
Cross-functional teams can greatly facilitate the successful implementation of projects. This study examined the influence of a set four antecedent constructs (superordinate goals, accessibility, physical proximity and formalized rules and procedures) on the attainment of both cross-functional cooperation and perceived project outcomes. Through the use of path analysis, the results indicated that superordinate goals, physical proximity and project team rules and procedures have significant direct and/or indirect effects on project outcomes through influencing cross-functional cooperation. Further, cross-functional cooperation was a significant predictor of both perceived task and psychosocial project outcomes. Directions for management practice and future research are discussed.